Interdisciplinary insights into paleoenvironments of the Queen Charlotte Islands/Hecate Strait region - Hetherington, Renée (2002)
Subsequent to the Last Glacial Maximum (LGM), complex coastal response resulted from deglaciation, eustatic sea-level change, and a relatively thin, flexible lithosphere in the Queen Charlotte Islands (QCI) region of northwestern Canada. Presented here is an interdisciplinary study that combines the methodologies and schools of thought from geology, biology, and geography to address a research problem that spans these disciplines, specifically to illustrate the environment, temporal and spatial dimensions of isostatic crustal adjustment and the Late Quaternary coastline of the northeast Pacific continental shelf. Molluscan distribution, lithology, and published sub-bottom profiles are used to deduce sea-levels, outline the influence of glacially-induced crustal displacement, and reconstruct the paleoenvironment of the northeast Pacific Late Quaternary coastline, including the absence of ice and the presence of emergent coastal plains. These data are used to ascertain the region's suitability as a home for an early migrating coastal people. A series of paleogeographic maps and isostatic crustal displacement maps chart the sequence of evolving landscapes and display temporal changes in the magnitudes and extent of crustal flexure as a forebulge developed. The wave-length and amplitude of the glacially-induced forebulge supports thermal and refraction modeling of a thin (~25 km thick) lithosphere beneath Queen Charlotte (QC) Sound and Hecate Strait. Glacial ice at least 200 m thicker than present water depth began retreating from Dixon Entrance after 14,000 and prior to 12,640 14C years BP, generating 50 m of uplift in northern Hecate Strait. The position of the forebulge remained essentially constant after 12,750 14C years BP, implying a fixed ice-front and continued ice presence on the British Columbia (BC) mainland until ~10,000 14C years BP. A 3-dimensional model shows two ice-free terrains emerged: one extended eastward from the QCI, the other developed in QC Sound. By ~11,750 14C years BP a landbridge ...